Factors Associated With the Use of the Contraceptive Implant Among Women Attending a Primary Health Clinic in Cape Town, South Africa - Jonas, Kim; Mazinu, Mikateko; Kalichman, Moira; Kalichman, Seth; Lombard, Carl; Morroni, Chelsea; Mathews, Catherine (Frontiers in Global Women's Health, 2021)
Background: Long-acting reversible contraceptives (LARCs), which include the subdermal contraceptive implant and intrauterine contraception, offer women safe, highly effective, long-term pregnancy prevention, and expanded contraceptive options. The implant greatly expands LARC options for South African women as it is available free of charge at public health facilities, but we know little about factors associated with its uptake. This study describes factors associated with the intention to use the implant, including knowledge and beliefs about the implant and perceived outcome expectancies of implant use among women Cape Town, South Africa. Methods: Between 2015 and 2016, we conducted a quantitative, cross-sectional survey among adult women attending a public, primary health clinic in Cape Town, South Africa between. Using a structured questionnaire, we measured women’s knowledge, awareness and attitudes towards, perceived outcome expectancy, and the intention to use the contraceptive implant in future among the women. Results: We surveyed 481 women (mean age 29.1 years). Most (n=364, 75.6%) had heard about the implant, 45 (9.4%) were currently using it and 97 (20.2%) intended to use it in the future. Knowledge about the safety of the implant, beliefs about its effectiveness and the ease of insertion and removal, and support from intimate partners were positively associated with the current use and intentions to use the implant in the future. Conclusions: Limited knowledge of the implant, having completed secondary schooling, partner’s support for women to use implant and the perceived outcome expectancies of using the implant were factors significantly associated with intention to use the implant. Ensuring that contraception information is available in all South African languages regardless of women’s education levels, and that comprehensive contraception education and counselling is provided during all family planning might help improve the uptake of contraceptives, include the use of the implant in the country.